2009
DOI: 10.2989/ajas.2009.34.3.5.981
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation, growth rate and size at sexual maturity of tigerfishHydrocynus vittatusfrom the Okavango Delta, Botswana

Abstract: The aims of this study were to determine relative age, growth rate and size at maturity of tigerfish in the Okavango Delta as a basis for the development of a fisheries management plan. A total of 206 tigerfish Hydrocynus vittatus, collected by angling in August 2005, 2006 and 2007, was assessed for sexual maturity and relative ages were estimated from 135 of these, using scales and whole and sectioned otoliths. Sectioned otoliths were the most appropriate method for ageing H. vittatus of up to 20 years old. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The noticeable macroscopic characteristics during the various maturity stages of the testes have been recorded in Table . This table was developed specifically for the maturity identification of the testes from C. gariepinus (adapted from the features described by Cambray, , Booth & Weyl, and Gerber et al, ).The most prominent characteristic during the developing spermatogenic stages was the white ‘wavy fringe’ on the lateral region of the testes (Pieterse, Marchand, Dyk, & Barnhoorn, ; Wagenaar, Botha, & Barnhoorn, ). This area develops and becomes more prominent as more developing germ cells mature into spermatozoa during the late spermatogenic stage (Nibamureke, Barnhoorn, & Wagenaar, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The noticeable macroscopic characteristics during the various maturity stages of the testes have been recorded in Table . This table was developed specifically for the maturity identification of the testes from C. gariepinus (adapted from the features described by Cambray, , Booth & Weyl, and Gerber et al, ).The most prominent characteristic during the developing spermatogenic stages was the white ‘wavy fringe’ on the lateral region of the testes (Pieterse, Marchand, Dyk, & Barnhoorn, ; Wagenaar, Botha, & Barnhoorn, ). This area develops and becomes more prominent as more developing germ cells mature into spermatozoa during the late spermatogenic stage (Nibamureke, Barnhoorn, & Wagenaar, ).…”
Section: Resultsmentioning
confidence: 99%
“…Using criteria previously described by Cambray(), Booth and Weyl () and GerberSmit and Pieterse (), as guideline, the macroscopic and microscopic maturity stages of the testes of each fish were determined. Criteria for this assessment specific for male C. gariepinus were recorded and tabulated (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Although it is difficult to infer the size of individuals based on isolated teeth, mature teeth of Nsungwe Hydrocynus sample compare favorably in size with immature individuals of H. vittatus (287 § 13 mm fork length; Gagiano et al, 1996) but not mature individuals (males >451 mm and females >522 mm total length; Gerber et al, 2009). It is tempting to suggest the presence of a smaller species or population of exclusively immature individuals, but specimens hail from well-sorted coarse-grained sandstones and therefore may simply reflect depositional environment.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Skelton (2001) has shown that southern African female tigerfish are generally heavier than males. This is certainly true for the Okavango, where in a sample of 208 tigerfish (~1:1 male:female ratio), all fish larger than 2 kg were female (see Gerber et al [2009] for data on fish lengthweight relationship and size at sexual maturity). Our data demonstrate that blood lactate increased with angling duration, up to approximately 6 mMol l -1 at 3-4 minutes.…”
Section: Angling Duration Versus Fish Sizementioning
confidence: 99%